Quality, morphometry and mineral composition of Agave spp. seeds in Oaxaca - Sánchez-Celaya, Neftalí; Ruiz-Luna, Judith; Velasco-Velasco, Vicente Arturo; Martínez-Martínez, Raquel; Guzmán-Sebastián, Karen del Carmen; De los Santos-Romero, Rodolfo Benigno (Revista Mexicana de Ciencias Agrícolas, 2026)
The seed is a reproductive organ of vascular plants from which a new individual is generated. Quality tests were conducted on seeds of five agave species, and morphometry and nutritional content were determined; the latter was compared with the soil’s mineral content. The collection of seeds and soil was carried out in some localities in the Central Valleys and Mixteca regions of Oaxaca during 2024. A. potatorum and A. salmiana presented the highest germination values, with 65.5% and 58.3%, respectively; A. americana significantly showed the highest weight of 1 000 seeds, with 11.2 g ±0.96; in moisture content, A. salmiana and A. karwinskii showed higher values. A. nussaviorum presented the highest weight gain with 389.4%; in the determination of viability, A. potatorum reflected the highest value with 72.8%. In the morphometric analysis, a cumulative variation of 61.1% was detected, with an overlap of ellipses between the species. A higher concentration of Zn, Fe, and Na was found as predominant elements in the seed; their values were not related to the concentration in the soil. The soil’s physical and chemical characteristics were diverse. In a principal component analysis with all variables, the first three components accounted for 89% of the total variance. With this methodology, the variables that reduce dimensionality were identified, giving greater significance to certain minerals.